AI-Powered Language Learning Tools and Their Impact on EFL Students’ Speaking Anxiety in Jordanian Universities - Wardat, Saja; Akour, Mohammed (Journal of Posthumanism, 2025)
Speaking anxiety is a persistent challenge for English as a Foreign Language (EFL) students, impacting their fluency, confidence, and academic performance. This study investigates the influence of AI-powered language learning tools on speaking anxiety among Jordanian university students. A survey of 200 students assessed key anxiety factors, coping strategies, AI tool adoption, and barriers to AI integration. Statistical analysis, was used to compare AI users and non-users. Results indicate that while AI tools do not significantly reduce students’ fear of making mistakes or fear of others’ reactions, they do have a significant impact on reducing academic pressure. Furthermore, institutional and technological barriers remain primary obstacles to AI adoption. These findings indicate that incorporating AI into EFL instruction should be accompanied by well-structured language support programs to enhance its impact. The study provides insights into how AI can be used alongside traditional TESOL methods to help reduce speaking anxiety.